Household Financial Management In Household Women In Emplasmen Aeknabara Village, Bird Hulu District, Labuhan Batu District - Nova Indriyani; Yudi Prayoga; Bhakti Helvi Rambe (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Community Service for Household Financial Management aims to increase knowledge in broadening the understanding of housewives when recording family financial management. A household certainly has the goal of a financially prosperous family, with prosperous finances, of course, the financial management that occurs in the family must have carried out good and efficient financial planning. Financial conditions that are already prosperous must have a savings or investment fund, this is because it will have an impact on the future life of the family. The method used when carrying out this activity is using training and discussion sessions or questions and answers on the elaboration of household financial management. Housewives were trained by giving one problem illustrating a family, of the 15 participants who attended they were very active and responded to the ongoing training activities on the questions they were working on. Participants in the activity, namely housewives as financial managers in a family, must understand the concept of financial planning in the future, to turn a family into a prosperous family.